NK1.1+ cells promote sustained tissue injury and inflammation after trauma with hemorrhagic shock. Issue 1 (17th May 2017) - Chen, Shuhua; Hoffman, Rosemary A; Scott, Melanie; Manson, Joanna; Loughran, Patricia; Ramadan, Mostafa; Demetris, Anthony J; Billiar, Timothy R
Abstract : NK1.1+ cell activation contributes to the persistence of inflammation leading to end organ damage in the liver and gut after HS/T. Abstract: Various cell populations expressing NK1.1 contribute to innate host defense and systemic inflammatory responses, but their role in hemorrhagic shock and trauma remains uncertain. NK1.1 + cells were depleted by i.p. administration of anti-NK1.1 (or isotype control) on two consecutive days, followed by hemorrhagic shock with resuscitation and peripheral tissue trauma (HS/T). The plasma levels of IL-6, MCP-1, alanine transaminase (ALT), and aspartate aminotransferase (AST) were measured at 6 and 24 h. Histology in liver and gut were examined at 6 and 24 h. The number of NK cells, NKT cells, neutrophils, and macrophages in liver, as well as intracellular staining for TNF-α, IFN-γ, and MCP-1 in liver cell populations were determined by flow cytometry. Control mice subjected to HS/T exhibited end organ damage manifested by marked increases in circulating ALT, AST, and MCP-1 levels, as well as histologic evidence of hepatic necrosis and gut injury. Although NK1.1 + cell–depleted mice exhibited a similar degree of organ damage as nondepleted animals at 6 h, NK1.1 + cell depletion resulted in marked suppression of both liver and gut injury by 24 h after HS/T. These findings indicate that NK1.1 + cells contribute to the persistence of inflammation leading to end organ damage in the liver and gut.